БЕРДАҚНИНГ «ШАЖАРА» ДОСТОНИДА ОБРАЗЛАРНИНГ ЯРАТИЛИШИ - Утамбетова, А. (SCIENCE and SOCIETY, 2018)
The article deals with the actual questions of the Karakalpak folklore and literature which haven't been investigated enough yet. The author of the research studies from the point of view of the historical-realistic aspect the issues of Karakalpak folklore in the XVIII-th century in comparison with the poem "Shejire" ("Pedigree") by the classic of the Karakalpak literature Berdakh.
Keywords: poem; shejire; image; real; artistic; to create